Profil Keterampilan Metakognitif Mahasiswa Calon Guru Biologi di Universitas Muhammadiyah Bone - Romi Adiansyah (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2022)
Metacognitive skills assist pupils in achieving learning independence. The present study aimed to identify the metacognitive skill profile of pre-service biology teachers at Universitas Muhammadiyah Bone in South Sulawesi, Indonesia. This quantitative descriptive study involved 50 Biology students from Universitas Muhammadiyah Bone in South Sulawesi. The students were randomly selected from all students enrolled in the university’s biology education study program. The study took place in November 2021. Essay questions were used to assess the participants’ metacognitive skills, while the metacognitive awareness inventory (MAI) was used to measure the participants’ metacognitive awareness. According to data analysis, 8% of pre-service biology teachers have well-developed metacognitive skills, 28% have developing metacognitive skills, 48% have “start to develop” metacognitive skills, and 16% have “very risky” metacognitive skills. Meanwhile, the metacognitive awareness scores for pre-service teachers on planning, monitoring, evaluating, and revising were 58.56, 49.87, 42.39, and 37.73, respectively. These scores are classified as low. Thus, metacognitive skills of the students must be fostered using active and innovative learning models. The findings of this study provide insights for future research on how to improve the quality of prospective biology teacher graduates as they prepare to teach in the twenty-first century and the era of digital globalization. Keywords: profile, metacognitive skills, pre-service biology teachers